2017
DOI: 10.1016/j.ijfatigue.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the fatigue strength of thin-plates in large structures

Abstract: This paper studies the main factors affecting the fatigue strength assessment of thin plates in large structures. The first part of study includes the influence of initial distortions, joints' flexibility and surrounding structure on structural stress analysis of welded joint. The second part covers the influence of joint and its geometrical properties on fatigue strength modelling. The third part includes also the material elastic-plastic behaviour and the influence of crack propagation. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In marine design, for instance, thick monolithic plates can be replaced with sandwich panels made from thin plates to achieve a weight reduction. These lightweight structures made of thin plates pose new engineering challenges: the current methods to estimate the fatigue life of steel structures were developed for thick plates, and their application to thin plates raised a new set of challenges [1][2][3][4][5], such as prober consideration of joint geometry and stress gradient at critical weld notch [6,7], in addition to other well-known difficulties [8][9][10]. In steel sandwich structures, the thin plates are assembled together by means of a laser welding process, and the sandwich panel consists of laser stake-welded T-joints, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In marine design, for instance, thick monolithic plates can be replaced with sandwich panels made from thin plates to achieve a weight reduction. These lightweight structures made of thin plates pose new engineering challenges: the current methods to estimate the fatigue life of steel structures were developed for thick plates, and their application to thin plates raised a new set of challenges [1][2][3][4][5], such as prober consideration of joint geometry and stress gradient at critical weld notch [6,7], in addition to other well-known difficulties [8][9][10]. In steel sandwich structures, the thin plates are assembled together by means of a laser welding process, and the sandwich panel consists of laser stake-welded T-joints, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by energy efficiency and fuel economy reasons, the structural lightweight design for large-size structures has been in the spotlight of the recent research in several industrial fields. For instance, modern cruise ships have been designed to accommodate an increased number of cabins and open spaces, thus directing shipbuilding towards new solutions in terms of space and weight in order to increase the performance of the structure [1][2][3][4][5]. Thinwalled structures represent an optimum solution to achieve this design target.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue strength assessment is one of the key challenges, as thin structures show considerable susceptibility to manufacturing-and assembly-induced imperfections [6]. According to Remes et al [4], a visible detrimental effect on the fatigue life of thin-walled marine structures is caused by welding. It has been demonstrated that less severe distortions may be obtained by low-heatinput welding methods such as laser-hybrid welding [1,3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Weight reduction of large steel structures is possible using advanced steel materials. The efficient utilization of new material and the lightweight solution requires high manufacturing quality and robust design methods 1,2 . A robust design method means structural analysis under realistic loading conditions, such as wave-induced loading in the case of a cruise ship, as well as response calculations to define deformation and stresses.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key design challenges for new lightweight solutions is fatigue due to its cumulative and localized nature, often taking place at weld notches. For high manufacturing quality, the fatigue behavior is dominated by small fatigue crack (SFC) growth since manufacturing induced defects are very small 1,3 . Thus, the fundamental understanding of small fatigue crack growth in metallic materials is crucial for sustainable use of new steels in high performance structures.…”
Section: Introductionmentioning
confidence: 99%